P4 Cause specific child and young person mortality in the UK and EU15+ countries. (May 2019) - Ward, JL; Wolfe, I; Viner, RM
Abstract : Background: UK all-cause mortality outcomes for children and young people (CYP) are worse than in similar wealthy nations, although little is known about comparative differences in cause specific mortality. Methods: We used mortality estimates coded from the WHO World Mortality Database to compare UK outcomes with EU15 +countries (European Union countries pre-2004 plus Norway, Australia and Canada). Causes of death were mapped using the Global Burden of Disease mortality hierarchy to 21 level 2 cause groups. We used poisson regression models to compare UK mortality for 1–9 and 10–19 year olds with EU15 +countries in 2015. We then ranked the UK for each cause by 5 year age group and sex compared with EU15 +countries in 2015, and report change in rank since 2010. Results: The incidence rate ratio (IRR) for number of deaths in the UK in 2015 was significantly higher for common infections, chronic respiratory conditions and digestive disorders (1–19 year olds), and neurological conditions and diabetes/urological/blood or endocrine conditions (10–19 year olds). UK mortality was significantly lower than EU15 +countries for transport injuries and self-harm/violence for 10–19 year olds. Relative to other EU15 +countries, the UK had the highest to third highest mortality in 2015 for common infections in both sexes and all age groups, and in 8 out of 10 non-communicable disease (NCD) causes in both sexes in at least one age group. The UK ranked in the best 5 countries for most injury outcomes, but had dropped rank since 2010 for self-harm/violence (both sexes) and unintentional injuries amongst males. Conclusion: UK mortality in CYP is higher than a comparable group of wealthy countries for common infections and multiple NCD causes. Although the UK performed well for injury mortality, this position appears to be eroding. There is an urgent need to explore social, economic and health service factors which may be contributing to these differences in mortality outcomes.